Perancangan Tata Letak Gudang Barang Jadi Produk Jilbab dengan Metode Class Based Storage dan Penataan Ergonomis CV Jilbab Surabaya - Mohamad Syihabul Akbar; Karunia Wati, Putu Eka Dewi (SURYA TEKNIKA, 2024)
CV Jilbab Surabaya is a company that makes and sells rectangular hijabs, Pashmina hijabs, Bergo hijabs, and others. The storage warehouse has dimensions of 17 m long, 8 m wide and 6 m high. Knowing how to prepare the proposed layout using the class based storage method, knowing the product arrangement time, and knowing the shelf investment and labor using flexsim simulation. This research work activity was carried out for 4 months starting from October 1 2023 to January 31 2024. From the results of ABC classification processing on 20 types of hijab products in finished goods storage at CV Jilbab Surabaya: class A 68.92%, 26 products, class B 14.72%, 8 products, and class C 16.09%, 11 products. In the proposed layout using flexsim, it was found that the average waiting time for the three employees was 7.07 seconds with items arranged neatly using the class based storage method.